Isolation and characterization of the fungus Moniliopthora roreri (Cif) H.C. Evans, Stalpers, Samson & Benny. (1978). of fruits of Theobroma cacao L. (Revista Torreón Universitario, 2022)
This scientific trial was carried out to isolate and characterize the fungus Moniliophthora roreri (CIF) H.C.Evans, Stalpers, Samson & Benny. ( 1978) phytopathogen that causes great economic losses when spread on fruits of Theobroma cacao L the sampling was carried out in the farm named “El Mango” located 11°10´02°N 84°25´53°W in the municipality of Castillo, department of Rio San Juan, Nicaragua property of Mr. José Leonel Gómez Álvarez, For the isolation of the fungus Moniliophthora roreri  (CIF) H.C.Evans, Stalpers, Samson & Benny. (1978) cocoa samples were collected with symptoms of Moniliophthora roreri (CIF) H.C.Evans, Stalpers, Samson & Benny. ( 1978) and was characterized in microscopes.
Keywords: Isolation; Spores; Morphology